An Analysis 0f Figurative Language Used in “Up All Night Album 2011” by One Direction - I Gusti Ngurah Bagus Yoga Widiadnya, (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
This research aims to find out the types and meaning of figurative language used in “Up All Night album 2011” by One Direction and to describe the meanings conveyed from the figurative language used in “Up All Night album 2011” Sung by One Direction. The researcher used the theory from Leech to find out the types of figurative language. This study used a qualitative descriptive method to find out the types of figurative language and the meaning of figurative language. The result of this research there are 7 types of figurative language found in Up All-Night album 2011. Based on the data 40 lyrics contains figurative language, those are: hyperbole 3 data, irony 1 data, metaphor 1 data, metonymy 3 data, personification 1 data, simile 3 data, and repetition of 29 data and 11 lyrics contains meaning, they are Conceptual meaning 5 data, Connotative Meaning 4 data, and Affective Meaning 2 data. This research is expected to contribute as a medium for learning because there are so many enthusiasts in listening to music. After all, music will be more interesting, relaxing, and have a high score in language style.